2017
DOI: 10.1016/j.fertnstert.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Increasing awareness of age-related fertility and elective fertility preservation among medical students and house staff: a pre- and post-intervention analysis

Abstract: Despite professional and personal interest, knowledge of age-related fertility decline and elective fertility preservation is limited among medical students and house staff. This study highlights the need for formal education across all levels of training and specialties, with even brief interventions being of potential benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…The length of exposure to a formal REI program did not affect comfort in counseling patients in EF, indicating that brief focused REI rotations exposing residents to Assisted Reproductive Technology could help improve patient access to OB/GYN physicians who are comfortable in discussing EF. This finding supports Anspach-Will et al’s interventional study, which found that an hour-long educational session on EF was sufficient to significantly improve medical professionals’ knowledge-based scores about EF [3] and suggests that a brief but focused curriculum in EF could help improve resident confidence in discussing EF with patients. Female residents’ input regarding what they consider important for prospective patients to know could also guide training on EF.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The length of exposure to a formal REI program did not affect comfort in counseling patients in EF, indicating that brief focused REI rotations exposing residents to Assisted Reproductive Technology could help improve patient access to OB/GYN physicians who are comfortable in discussing EF. This finding supports Anspach-Will et al’s interventional study, which found that an hour-long educational session on EF was sufficient to significantly improve medical professionals’ knowledge-based scores about EF [3] and suggests that a brief but focused curriculum in EF could help improve resident confidence in discussing EF with patients. Female residents’ input regarding what they consider important for prospective patients to know could also guide training on EF.…”
Section: Discussionsupporting
confidence: 83%
“…Despite their central role in counseling patients on EF, little is known about medical trainees’ views on the procedure. Among medical students and house staff with prior knowledge of EF, 80% reported acquiring this knowledge through their formal education [3], indicating that EF is not well-covered in medical schools. A survey of U.S. Obstetrics and Gynecology (OB/GYN) residents indicated that 83% felt that they should begin conversations with their patients regarding fertility, and most felt that these conversations should occur during annual exams [4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Anspach et al surveyed medical students and house staff on their professional and personal perception of fertility before and after an educational intervention. They found that both groups increased their score post-intervention in the knowledge-based questions [35]. While this study assessed a distinct population of medical students and staff, it demonstrates the value of education to promote fertility-related knowledge.…”
Section: Discussionmentioning
confidence: 67%
“…Awareness of OFNMR was consistently evident in a significant proportion (over 75%) of women in five studies 21,23,25,28,29 . In four other included studies the reported rates of awareness were lower, 18,30‐32 with only 34% of students having heard of the procedure in one study conducted in Italy 32 .…”
Section: Resultsmentioning
confidence: 87%